Mobilisasi Dini Sebagai Intervensi Keperawatan Terhadap Proses Penyembuhan Luka Pasca Seksio Sesarea - Enok Nurliawati; Etty Komariah Sambas; Livia Raissa Shalehah (Jurnal Keperawatan Galuh, 2025)
A cesarean section is a surgical procedure performed to deliver a baby through an incision in the abdomen and uterine wall. The prevalence of cesarean sections continues to rise both in Indonesia and worldwide. However, postoperative incisional wounds after cesarean delivery lead to various risks that can hinder the healing process. One nursing intervention that can help speed up wound healing is early mobilization. This study aimed to analyze the relationship between early mobilization and wound healing in post-cesarean section patients. A descriptive correlational design with a cross-sectional approach was used in this study. Respondents were selected through purposive sampling, with a total of 178 participants. Statistical analysis was conducted using the chi-square test. The results showed a significant association between early mobilization and wound healing (p = 0.025), indicating that patients with inadequate early mobilization had a 2.17 times greater risk of poor wound healing (OR = 2.17). Early mobilization was proven to speed up wound healing after cesarean section. Therefore, nurses should ensure and support early mobilization in post-cesarean section patients.